Enterobacteriaceae in calves, cows and milking environment may act as reservoirs of virulence and antimicrobial resistance genes - de ALMEIDA, Camila Chioda [UNESP]; Financi, Thaylane Paula [UNESP]; Cardozo, Marita Vedovelli [UNESP]; Pizauro, Lucas Jose Luduverio [UNESP]; Pereira, Natalia [UNESP]; Valmorbida, Mylena Karoline [UNESP]; Borzi, Mariana Monezi [UNESP]; Weiss, Bruno [UNESP]; de ÁVILA, Fernando Antônio [UNESP] (FapUNIFESP (SciELO), 2021)
The aim of this study was to investigate the presence of virulence and antimicrobial resistance genes and clonal profile of Enterobacteriaceae isolated from calves, cows, feeding buckets and the milk bucket. A a total of 31 Enterobacteriaceae isolates from calves (6), milk bucket (6), feeding buckets (6) and from cows’ rectum (13) were used. The presence of LT, STa, STb, STx1, STx2, eae, rmpA, wabG, mrkD, kfu, mcgA, fimH and uge as well as the antimicrobial resistance genes: AmpC MOX, FOX, MIR, ACT, DHA, ACC, CTX-M-1, CTX-M2, TEM KPC and MCR-1 and SH were evaluated by PCR. The LT toxin gene were detected in five isolates (16.1%) and the mrkD gene was detected in three isolates (9.0%). The CTX-M-1 gene was detected in 13 isolates (41.9%), CTX-M-2 in five isolates (16.1%) and ACC-M in four isolates (12.9%). Most of the isolates obtained demonstrated, resistance to cephalothin (87.5%), ampicillin, (87.5%) and streptomycin (84.3%) with multidrug resistance observed in all isolates. Isolates from bucket and cow’s rectum, calves and milk bucket, calf and cow’s rectum shared the same pulsotypes. These findings may suggest that enterobacteria carring virulence and resistance genes may persist in the environment and became a reservoir of these genes.
Keywords: Antibiotic; E. coli; K. pneumoniae; Milk